Preferential frequency and size effect of the Brownian force acting on a nanoparticle. (5th September 2017) - Jin, Hanhui; Liu, Ningning; Ku, Xiaoke; Fan, Jianren
Abstract : The Brownian motion of a nanoparticle in fluid depends on the molecular forces acting on it. Because of the small size and the high frequency, it is difficult to make experimental measurements of these forces. In the present work, Brownian forces acting on a nanoparticle are numerically investigated with the molecular dynamics method. Some new phenomena are disclosed. (i) The probability distribution shows that the Brownian forces conform to the Gaussian distribution and self-similarity of the probability distribution is also found for different 1/Kn numbers which are characterized with the particle radius and the mean path [STIX]x1D706 of the gas molecule (1/Kn=R/[STIX]x1D706) . (ii) The frequency spectrum distribution of the Brownian force is not a white noise spectrum, which is different from the assumption commonly used in Langevin model. The preferential frequency of the Brownian force is found. (iii) The size effect relating to the Brownian forces is not monotonically varying with 1/Kn=R/[STIX]x1D706 and is also found. It first increases and then decreases after it reaches the maximum value at 1/Kn≈ 250 . The variation process for 1/Kn<250 observed in the present work has not been reported in previous research to date.